COMPUTER-TOMOGRAPHIC TECHNOLOGIES IN THE SURGERY OF ADRENAL GLANDS - N. A. Maistrenko; I. S. Zheleznyak; P. N. Romashchenko; S. G. Blyumina (Вестник хирургии имени И.И. Грекова, 2016)
The reasonability of application computed tomography (CT) in differential diagnostics of adrenal tumors and navigation of rational surgical approach for adrenalectomy was specified by possibilities of method development. The special research of CT possibilities in adrenal tumor diagnostics and substantiation of choice of surgical interference were made in 188 patients. An analysis of clinical-laboratory and instrumental data allowed diagnostics of aldosteroma in 26% patients, corticosteroma in 33,0%, chromaffinoma in 24,5%, adrenocortical cancer in 8,5%, hormonally inactive tumor in 8,0%. Results of morphological investigations of removed adrenal tumors were matched with the preoperative CT data. There was revealed a certain density of tumors. On the basis of this density and clinical-laboratory data, the authors could reliably make a diagnosis the disease before the operation, which is very important in asymptomatic illness course and subclinical manifestations.